"Petit Spot" Rejuvenated Volcanism Superimposed on Plume‐Derived Samoan Shield Volcanoes: Evidence From a 645‐m Drill Core From Tutuila Island, American Samoa. (21st March 2019) - Reinhard, Andrew A.; Jackson, Matthew G.; Blusztajn, Jerzy; Koppers, Anthony A. P.; Simms, Alexander R.; Konter, Jasper G.
Abstract: In 2015 a geothermal exploration well was drilled on the island of Tutuila, American Samoa. The sample suite from the drill core provides 645 m of volcanic stratigraphy from a Samoan volcano, spanning 1.45 million years of volcanic history. In the Tutuila drill core, shield lavas with an EM2 (enriched mantle 2) signature are observed at depth, spanning 1.46 to 1.44 Ma. These are overlain by younger (1.35 to 1.17 Ma) shield lavas with a primordial "common" (focus zone) component interlayered with lavas that sample a depleted mantle component. Following ~1.15 Myr of volcanic quiescence, rejuvenated volcanism initiated at 24.3 ka and samples an EM1 (enriched mantle 1) component. The timing of the initiation of rejuvenated volcanism on Tutuila suggests that rejuvenated volcanism may be tectonically driven, as Samoan hotspot volcanoes approach the northern terminus of the Tonga Trench. This is consistent with a model where the timing of rejuvenated volcanism at Tutuila and at other Samoan volcanoes relates to their distance from the Tonga Trench. Notably, the Samoan rejuvenated lavas have EM1 isotopic compositions distinct from shield lavas that are geochemically similar to "petit spot" lavas erupted outboard of the Japan Trench and late stage lavas erupted at Christmas Island located outboard of the Sunda Trench. Therefore, like the Samoan rejuvenated lavas, petit spot volcanism in general appears to be related to tectonic uplift outboard of subduction zones, and existing geochemical data suggest that petit spots share similar EM1 isotopic signatures. Key Points: Within the 645‐m Tutuila drill core we find isotopically heterogeneous lavas as well as several abrupt temporal and geochemical boundaries The proximity of Samoan volcanoes to the Tonga Trench and geochronology are consistent with a tectonic influence on rejuvenated volcanism The tectonic setting and isotopic signatures of the Samoan rejuvenated lavas link them to "petit spots" outboard of the Japan Trench